2021
DOI: 10.3389/fped.2020.570535
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Loneliness Among Chinese Caregivers of Children With Chronic Kidney Disease During the COVID-19 Pandemic: A Propensity Score Matching Analysis

Abstract: To evaluate social support and loneliness as well as their association among caregivers of children with chronic kidney disease (CKD) from China during the coronavirus disease 2019 (COVID-19) pandemic. We collected data for caregivers of children with CKD and caregivers of healthy children and matched the two groups using propensity score matching (PSM). We compared the differences in social support and loneliness between the two groups after matching and analyzed the relationship between social support and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…In the data concerning the instruments, it was noted the predominance of patients with moderate level of loneliness (55%), with 23.8% of patients with low level of loneliness, followed by 21.3% of patients with high level of loneliness. This number is consistent with all the theory addressed in this study, characterizing CKD also as a social problem due to its necessary adaptation in the autonomy of basic activities of daily living and by social withdrawal after the beginning of treatment (O'Hare et al, 2018;Shi et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the data concerning the instruments, it was noted the predominance of patients with moderate level of loneliness (55%), with 23.8% of patients with low level of loneliness, followed by 21.3% of patients with high level of loneliness. This number is consistent with all the theory addressed in this study, characterizing CKD also as a social problem due to its necessary adaptation in the autonomy of basic activities of daily living and by social withdrawal after the beginning of treatment (O'Hare et al, 2018;Shi et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…These feelings directly affect patients' quality of life and highlight the importance of good social monitoring, the need for good hospital service, and increased attention from the health care team to result in improved health conditions. Finally, possible negative outcomes that can be prevented are highlighted in studies, as also presented in the study of Shi et al (2020), in which it was confirmed that good social interaction and minimal loneliness are associated with positive emotions, while less social support and greater loneliness are associated with insufficient self-care and reduced social interaction. Thus, studying the impact of loneliness and associated factors on the lives of hemodialysis patients becomes essential for the non-development and non-mortality of CKD.…”
Section: Introductionmentioning
confidence: 71%
“…In July or August 2020, essential family caregivers equipped with personal protective equipment were allowed to enter a resident's room. Loneliness, anxiety, and a sense of burden rose dramatically for family caregivers, regardless of the care setting [14,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Social support is a protective factor for caregivers of children with chronic diseases. Caregivers of children with chronic diseases have lower levels of social support and higher levels of loneliness than caregivers of healthy children (22,23). Parents of children with autism in developing countries experience greater stress than parents in developed countries, partly due to the lack of social support systems (24).…”
Section: Introductionmentioning
confidence: 99%